An interpenetrating amine-functionalized metal–organic framework as an efficient and reusable catalyst for the selective synthesis of tetrahydro-chromenes1. Issue 7 (21st February 2015) - Safarifard, Vahid; Beheshti, Saeideh; Morsali, Ali
<x xml:space="preserve">Abstract</x> An amine-functionalized metal–organic framework as an efficient heterogeneous catalyst for the selective synthesis of tetrahydro-chromenes.